Hukuman Kebiri: Analisis Maqashid Syariah dan Undang-Undang Nomor 70 Tahun 2020 - Amrullah Bustamam; Hari Rizky Putra (Islamic Criminal Law Department, Faculty of Sharia and Law, UIN Ar-Raniry, 2022)
Abstract: This study aims to present Maqashid Syariah's perspective on the pros and cons of the enactment of castration penalties for perpetrators of child sexual crimes in the Government Regulation in Lieu of Law No. 70 of 2020. This research is qualitative research in the form of literature studies. This type of Islamic law research with maqashid sharia approach. The results of this study aim to find out about the regulation of castration punishment in Perppu Number 70 of 2020 for perpetrators of child sexual crimes, and to find out how Islamic law with the Maqashid Syariah approach regarding castration punishment. In this study also presented pros and cons of this castration penalty, some allow and also some prohibit this of course this argument is based on the approach of Maqashid Syariah. The presence of sharia maqashid is certainly needed in formulating a rule that will be a foothold and become a benchmark for the survival of a law. The purpose of Islamic law is also always relevant wherever and whenever it exists in terms of dynamic and elastic. Chemical castration punishment certainly cannot be used as a single solution to overcome the problem of crimes of sexual violence against children, the need for awareness and cooperation of the community and government to deal with sexual crimes against children.Abstrak: Kajian ini bertujuan untuk menyajikan perspektif Maqashid Syariah tentang pro dan kontra pemberlakuan hukuman kebiri bagi pelaku kejahatan seksual terhadap anak didalam Peraturan Pemerintah Pengganti Undang-Undang Nomor 70 Tahun 2020. Penelitian ini merupakan penelitian kualitatif berupa studi pustaka. Jenis penelitian hukum Islam dengan pendekatan Maqashid Syariah. Hasil penelitian ini bertujuan untuk mengetahui tentang pengaturan hukuman kebiri dalam Perppu Nomor 70 Tahun 2020 bagi pelaku kejahatan seksual terhadap anak, dan untuk mengetahui bagaimana hukum Islam dengan pendekatan Maqashid Syariah mengenai hukuman kebiri ini. Didalam penelitian ini juga tersaji Pro dan Kontra terhadap hukuman kebiri ini, ada yang membolehkan dan juga ada yang melarang hal ini tentunya argumen ini didasari oleh pendekatan Maqashid Syariah. hadirnya maqashid syariah tentunya sangat dibutuhkan dalam merumuskan sebuah aturan yang akan menjadi pijakan dan menjadi tolak ukur bagi kelangsungan hidup suatu hukum. Tujuan hukum Islam juga selalu relevan dimanapun dan kapanpun keberadaanya dalam hal dinamis dan elastis. Hukuman kebiri kimia tentu tidak bisa dijadikan solusi tunggal untuk mengatasi permasalahan kejahatan kekerasan seksual terhadap anak, perlu adanya kesadaran dan kerjasama masyarakat dan pemerintah untuk menangani kejahatan seksual seksual terhadap anak.